REPRODUCTIVE DISORDER STUDIES USING RADIOIMMUNOASSAY (RIA) PROGESTERONE ON DAIRY CATTLE - Tjiptosumirat, Totti; Tuasikal, Bokky Jeane Tuasikal; LelananingtyasNuniek@batan.go.id, Nuniek (Jurnal Ilmiah Aplikasi Isotop dan Radiasi, 2013)
Two intensive systems of husbandry practices, Garut West Java and Yogyakarta Central Java, were chosen for this study. Both areas have been voluntarily made into a pilot farm for the application of RIA progesterone to improve reproductive performance. Five dairy cattle from Garut West Java, which according to Health Extension and Artificial Insemination Technicians anamneses and according to farmers who own the animal, were showing reproductive failure and were selected from those cattle for the study. Other fifteen dairy cattle from Yogyakarta area, with anamneses of having low reproductive performance, were also selected for this study. Milk progesterone sample were collected twice a week for five consecutive weeks period of time to follow the biological reproductive status of every animal, while samples from dairy cattle at Yogyakarta were collected three times post Artificial Insemination (AI) services, as according to Artificial Insemination Database Application (AIDA) procedure, to monitor the failure of AI, success rate of AI, and ovarian activities of the cattle. Result of the study in Garut shows that RIA progesterone indicates that animals need special treatments and most AI failed due to lack of historical information of the dairy cows. RIA progesterone leads to a suggestion that it can be use as a tool to monitor the reproductive disorder, as the recommendation made for those cows to anticipate reproductive disorder overcome the problems. Similar result found in Yogyakarta, which almost 50% of the observed animals failed to AI due to miss-estrus detection. Furthermore, from the RIA for milk progesterone, information of the reproductive disorder figures can be drawn and early suggestion could be made to anticipate losses. Overall, beside the reproductive historical record, RIA progesterone is important tool to be applied in the animal husbandry system in Indonesia as to improve the herd productivity and has an economical value to reduce operational cost at waiting period for feeding animal up to INS Rp 224,000 — 336,000 per head animal.